Last rights liquidating a company - Branch, Ben, 1943-; Ray, Hugh.; Russell, Robin, 1960-; Oxford eBooks (New York ; Oxford : Oxford University Press, 2007)
In clear and concise language, this text explains how to wind-down and bring to successful conclusion the liquidation of a company, where to find hidden values, and what problems to look for.
Description based on print version record.
Includes index.
Keywords: Liquidation -- United States; Electronic books